PREVALENCE AND RISK FACTORS OF TRYPANOSOMIASIS IN HORSES IN EAST SUMBA DISTRICT - Praing, Umbu Yabu Anggung; Apsari, Ida Ayu Pasti; Dharmawan, Nyoman Sadra (Buletin Veteriner Udayana, 2023)
This study aims to determine the prevalence and risk factors for trypanosomiasis in horses in East Sumba. The samples used were blood from 286 horses taken in the West and East Regions of East Sumba Regency. Blood sampling was carried out through the jugular vein. Diagnosis of trypanosomiasis is made by examining thin blood smears stained with 10% Giemsa. The risk factors for trypanosomiasis were studied by distributing specially designed questionnaires to farmers. The results showed that 2.10% of the samples were T rypanosoma evansi positive. The distribution of incidents spread to Lewa District (3.65%), Kota Waingapu District (1.72%), and Pahunga Lodu District (7.4%). The probability of trypanosomiasis infection based on the OR value is horse age more than 5 years (OR=3.185), availability/origin of drinking water (OR=2.821), method of rearing (OR=2.179), female sex (OR=1.256), location/origin of horses in the western region (OR=1.022), heavy livestock traffic (OR=0.979), and farmer's knowledge of surra (OR=0.222). Statistically these risk factors were not significantly different (P>0.05). Therefore, it is necessary to carry out active surveillance and control of trypanosomiasis in horses in East Sumba District. Further research is also needed with other diagnostic methods, such as the card agglutination test (CATT).